Analisis Pengaruh Return On Asset, Return On Equity dan Net Profit Margin terhadap Nilai Perusahaan Sub Sektor Pulp and Paper di BEI - Fayzha Oktavia; M. Rimawan (Lembaga Pengembangan Kinerja Dosen, 2025)
The significance of profitability in raising business value, especially in the pulp and paper subsector, which confronts efficiency and competition issues, is what drives this study. The main objective of this research is to investigate the effects of ROA, ROE and NPM on firm value as measured by PBV. Three firms listed on the Indonesia Stock Exchange between 2019 and 2023 are the subject of this research, which use a purposive selection strategy and an associative quantitative technique. Multiple linear regression and traditional assumption tests were used to evaluate the data. The findings indicate that NPM has no discernible impact on company value, although ROA and ROE do. The three factors all have a major impact on PBV at the same time.. The study concludes that the effectiveness in utilizing assets and equity is a primary consideration for investors in assessing firm value, whereas operational efficiency represented by NPM is not yet a determining factor. These results have real-world ramifications for business managers, who should concentrate on raising ROA and ROE to improve their standing with investors.